Impact of Chronic Otitis Media on Systemic Inflammation and its Correlation With Oral Mucosal Disorders - Muhammad Ilyas, Amna Rafique Abbasi, Sh. Sarmad Elahi, Aysha Nauman, Muhammad Tahir Shah, Muhammad Awais Samee, Farah Naz Tahir, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Chronic Otitis Media (COM) is a prevalent condition characterized by persistent inflammation ofthe middle ear, often leading to systemic